2004
DOI: 10.1002/0471142956.cy0618s30
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Antigen‐Specific T Cells Using MHC Class I and Class II Tetramers

Abstract: Major histocompatibility complex (MHC) tetramers typically consist of a fluorophore‐streptavidin complex and biotinylated soluble MHC molecules carrying a peptide of interest. Tetramers bind to T cell receptors (TCR) that recognize the MHC molecule/peptide combination with high specificity. Native MHC molecules are expressed as cell‐surface glycoproteins capable of binding a variety of peptides generated from the degradation of self and non‐self proteins for display to T cells. The human MHC gene locus is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We sensitized B6 females with 2W-OVA.BALB/c (H-2 d ) skins and then mated them with 2W-OVA.BALB/c (H-2 d ) males (Fig 1c). OVA-specific CD8 + T cells were identified by flow cytometry using double fluorophore-labeled OVA:K b tetramers; henceforth, these fetus-and graft-specific T cells are referred to as TFGS (26,27). We note that OVA expressed by the skin or F1 fetus is crosspresented by recipient/dam APCs, although it is possible that maternal APCs are cross-decorated with OVA:K b complexes from F1 cells, or that microchimeric fetal cells are presenting OVA:K b to maternal T cells (7,28).…”
Section: Pregnancy Induces the Expression Of Co-inhibitory Molecules ...mentioning
confidence: 99%
“…We sensitized B6 females with 2W-OVA.BALB/c (H-2 d ) skins and then mated them with 2W-OVA.BALB/c (H-2 d ) males (Fig 1c). OVA-specific CD8 + T cells were identified by flow cytometry using double fluorophore-labeled OVA:K b tetramers; henceforth, these fetus-and graft-specific T cells are referred to as TFGS (26,27). We note that OVA expressed by the skin or F1 fetus is crosspresented by recipient/dam APCs, although it is possible that maternal APCs are cross-decorated with OVA:K b complexes from F1 cells, or that microchimeric fetal cells are presenting OVA:K b to maternal T cells (7,28).…”
Section: Pregnancy Induces the Expression Of Co-inhibitory Molecules ...mentioning
confidence: 99%
“…To test whether semi-allogeneic pregnancy is possible in females harboring immunological memory to paternal antigens, we sensitized female C57Bl/6 (B6, H-2 b ) mice with male 2W-OVA.BALB/c (H-2 d ) skin transplantation (skinTx). Donor 2W-OVA.BALB/c mice constitutively express 2W-OVA, a recombinant model antigen, allowing endogenous OVA-specific CD8 + T cells from the recipient to be tracked via flow cytometry using fluorophore-labeled OVA:K b tetramers 18,19 . Recipient B6 mice rejected skin grafts within 10 days (data not shown), and at day 30+ post-transplantation, skin-sensitized females were mated with 2W-OVA.BALB/c males (Sensitized+Pregnancy) (Fig.…”
Section: Pregnancy Induces a Dysfunctional Phenotype In Memory Tfgsmentioning
confidence: 99%
“…The procedure, little changed since the original report, allows for the identification of T cells of interest on the basis of the binding specificity of their cell surface receptors for particular MHC-peptide complexes (16-18). Studies using MHC class I tetramers have demonstrated that current methods for enumerating Ag-reactive CD8 + T cells vastly underestimate the size of the Ag-specific, virally induced T cell repertoire (17,18).…”
Section: Introductionmentioning
confidence: 99%